The effect of sward surface height on the response to mixed grazing by cattle and sheep - Wright, Iain A.; Jones, J.R.; Davies, D.A.; Davidson, G.R.; Vale, J.E. (2006)
An experiment was conducted to examine the effects of mixed grazing of sheep plus cattle under continuous stocking of permanent pasture at different sward heights. The experiment had a 2 × 3 factorial design, with two sward surface heights (4-5 and 8-10 cm) and three combinations of animal species viz., sheep only, cattle only and sheep plus cattle. There were two replicate plots of each treatment combination and the experiment was conducted over 2 years consecutively. The sheep were Beulah Speckled Face ewes and their single Suffolk-cross lambs while the cattle were yearling Charolais-cross steers. Six ‘core’ steers and six ‘core’ ewes and their lambs grazed plots, as appropriately, while additional, non-experimental steers and ewes and their lambs were used to maintain sward heights. Each year the steers and the ewes grazed the pastures from May to October, while lambs were weaned and removed each year from the experiment in July. There was no significant effect of mixed grazing on live-weight gain of steers, but ewes had significantly higher live-weight gains on the sheep plus cattle treatment than on the sheep-only treatment (82 v. 61 g/day; P<0.001). The live-weight gain of the lambs was higher on the mixed grazing treatment than on the sheep only treatment on the 8-10 cm sward height treatment (243 v. 212 g/day; P<0.05) but there was no significant difference on the 4-5 cm sward height treatment (260 v. 250 g/day; P>0.05). The total output of live-weight gain per ha from steers, ewes and lambs was not significantly affected by animal species combination. It is concluded that while output per ha is not enhanced by mixed grazing by sheep and cattle when sward height is controlled, the live-weight gain of ewes is increased and the live-weight gain of lambs can be increased on taller swards.